Environment modelling for robot vision using kinect - Alam, Ahnaf Tabrez; Rakib, Bashir Ahmed; Hoque, Ekramul (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.